Combined experimental and density functional theory study on the Pd-mediated cycloisomerization of o-alkynylnitrobenzenes - synthesis of isatogens and their evaluation as modulators of ROS-mediated cell death - Ramana, Chepuri V.; Patel, Pitambar; Vanka, Kumar; Miao, Benchun; Degterev, Alexei (European Journal of Organic Chemistry, 2010)
Highly selective cycloisomerization of o-alkynylnitrobenzenes, leading to isatogens, has been achieved by employment of a Pd-II complex. This reaction is very general and functional-group-tolerant. The possible mechanism of this reaction was investigated with the help of DFT calculations. Three possible pathways - namely, the addition of the nitro group either in (i) 5-exo-dig or (ii) 6-endo-dig mode and (iii) halopalladation - and subsequent intramolecular events have been considered and studied in detail. These investigations revealed that pathway (i) is the favored route to isatogen formation. A preliminary screening of the available isatogens reveals the 2-alkylisatogens to be novel ROS scavengers capable of inhibiting cellular necroptosis.
Keywords: Anthranil; cyclization; Density functional calculations; isatogens; Nitro-alkyne cycloisomerization; Palladium

Computational investigation of the role of the iridium dihydrogen pincer complex in the formation of the cyclic pentamer (NH2BH2)(5) - Ghatak, Kamalika; Vanka, Kumar (Computational and Theoretical Chemistry, 2012)
Computational studies with density functional theory (DFT) and MP2 have been done to investigate the interaction between the iridium dihydrogen pincer complex: (POCOP)IrH2 (where POCOP = eta(3)-1,3(OPt-Bu-2)(2)C6H3) and NH2BH2, the immediate product of ammonia borane (NH3BH3) dehydrogenation. A mechanism has been proposed for an oligomerisation process at the metal centre that involves competition between (i) insertion of an NH2BH2 molecule into the (NH2BH2)(n) chain and (ii) termination of the chain leading to the formation of the cyclic (NH2BH2)(n) oligomer. The calculated Delta G values show that the competition favours insertion over termination for the cases n = 1 to n = 4 but favours termination for n = 5. The computational studies therefore indicate that the cyclic pentamer (NH2BH2)(5) would be formed during NH3BH3 dehydrogenation by the (POCOP)IrH2 catalyst, agreeing with experimental findings. The mechanistic understanding gained has implications for the facile regeneration of ammonia borane. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Ammonia borane; Hydrogen storage; Iridium pincer ligand catalyst; Mechanistic studies; Oligomerisation cycle

Can molecular cages be effective at small molecule activation? a computational investigation - Kuriakose, Nishamol; Vanka, Kumar (Inorganic Chemistry, 2013)
Several approaches have been investigated in recent years in the area of small molecule activation. The current work introduces a new concept in this field: that of molecular cages, containing only main group elements, serving to activate small molecules. Full quantum mechanical calculations employing DFT/SCS-MP2 methods indicate that recently synthesized Ga-N cage compounds would be excellent candidates for mediating in important reactions such as the catalysis of ammonia borane dehydrogenation. The current work therefore opens up exciting new possibilities in small molecule activation research.

Catalytic and DFT study of selective ethylene oligomerization by nickel(II) oxime-based complexes - Tayade, Kamlesh N.; Mane, Manoj V.; Sen, Suman; Murthy, C. N.; Tembe, Gopal L.; Pillai, S. Muthukumaru; Vanka, Kumar; Mukherjee, Soumen (Journal of Molecular Catalysis A-Chemical, 2013)
The reactivity of nickel(II) thiophenealdoxime complex (3) toward oligomerization of ethylene in the presence of an alkylaluminum co-catalyst has been studied. The complex was found to be a selective ethylene dimerization catalyst in the presence of co-catalysts such as methylalumoxane (MAO) and diethylaluminum chloride (DEAC). With DEAC, the productivity was considerably higher than with MAO. Under optimum conditions the productivity reaches 388 kg/mol catalyst/h/bar with DEAC whereas for MAO this value was 119 kg/mol catalyst/h/bar. Complex 3 displays good ethylene conversions of up to a maximum of 90% with exceptionally high alpha-selectivity for 1-butene (>99.5%) amongst C-4 products. Computational studies using density functional theory (DFT) were also carried out to ascertain the decomposition pathway for 3 as well as that for Ni(II) complex of the pyridine ketoxime ligand 2. The results suggest that loss of one of the two bidentate oxime ligands attached to the metal center through reaction with DEAC is likely for both 2 and 3. Further, calculations indicate that the subsequent decomposition step was significantly more probable for 3 than for 2 thus explaining why the pyridine ketoxime ligand bound nickel complex 2 was experimentally found to be more stable than the thiophene aldoxime bound nickel complex 3. Calculations also show that the proton of the -OH group (oxime) plays a major role in the stability of the molecules. This was confirmed experimentally by synthesizing the Ni(II) dichloro complex of Pyridine-2-carbaldehyde O-methyloxime 5 and reacting it with ethylene under similar conditions. 5 was found to be highly active even at low co-catalyst concentrations. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Butene-1; Ethylene dimerization; Ni(II) complex; Thiophene aldoxime

Can silylenes rival transition metal systems in bond-strengthening pi-back donation? a computational investigation - Pal, Amrita; Vanka, Kumar (Chemical Communications, 2014)
Full quantum chemical calculations with density functional theory (DFT) show that bond-strengthening back-donation to a pi-diborene, recently discovered for transition metal systems (Braunschweig and co-workers, Nat. Chem., 2013, 5, 115-121), would be just as favored for Main Group silylene complexes. This result not only shows the range and applicability of the bond-strengthening back-bonding interaction, but also showcases the capacity of silylene complexes to do new chemistry, such as the cooperative activation of carbon monoxide and carbon dioxide.

Can substituted allenes be highly efficient leaving groups in catalytic processes? a computational investigation - Kuriakose, Nishamol; Vanka, Kumar (Journal of Computational Chemistry, 2015)
There is considerable interest presently in the chemistry of allenes. The current computational investigation looks into the possibility of using allenes and their derivatives as leaving groups. As it is well known, leaving groups are significant in catalytic processes for generating the active site. A full quantum mechanical study using density functional theory shows that allenes and their derivatives can function as excellent leaving groups. Indeed, the calculations show that they can be several orders of magnitude more effective than existing ligands for this purpose. The modification of second generation Grubbs' catalysts with these ligands suggests that the allene ligand cases that would be most effective are those having electron withdrawing groups, especially those that have the potential for supramolecular interactions between the substituent groups in the free state. (c) 2015 Wiley Periodicals, Inc.
Keywords: allenes; carbones; Density functional theory; olefin metathesis; supramolecular interactions

Computational study of metal free alcohol dehydrogenation employing frustrated lewis pairs - Mane, Manoj V.; Rizvi, Masood A.; Vanka, Kumar (Journal of Organic Chemistry, 2015)
The catalysis of acceptorless alcohol dehydrogenation (AAD) is an important area of research. Transition metal-based systems are known to be effective catalysts for this reaction, but developing metal free catalytic systems would lead to highly desirable cheaper and greener alternatives. With this in mind, this computational study investigates design strategies than can lead to metal free frustrated Lewis pairs (FLPs) that can be employed for AAD catalysis. A careful study of 36 different proposed FLP candidates reveals that several new FLPs can be designed from existing, experimentally synthesized FLPs that can rival or be even better than state-of-the-art transition metal-based systems in catalyzing the alcohol dehydrogenation process.

Can main group systems act as superior catalysts for dihydrogen generation reactions? A computational investigation - Kuriakose, Nishamol; Vanka, Kumar (Dalton Transactions, 2016)
The protolytic cleavage of the O-H bond in water and alcohols is a very important reaction, and an important method for producing dihydrogen. Full quantum chemical studies with density functional theory (DFT) reveal that germanium based complexes, such as HCCMeArB(2)GeH (Ar = 2,6-(Pr2C6H3)-Pr-i), with the assistance of silicon based compounds such as SiF3H, can perform significantly better than the existing state-of-the-art post-transition metal based systems for catalyzing dihydrogen generation from water and alcohols through the protolysis reaction.

Can the solvent enhance the rate of chemical reactions through C-H/pi interactions? insights from theory - Jain, Shailja; Vanka, Kumar (Physical Chemistry Chemical Physics, 2019)
The current computational study with density functional theory (DFT) shows that the rate of chemical reactions can be influenced through non-covalent C-H/p interactions between substrates and the solvent. It is shown that intramolecular carbon-carbon interaction and CO2 activation by a low valent silicon complex are both favourably affected by the explicit presence of the solvent toluene, due to C-H/p interactions between toluene and the silicon complex. Furthermore, ab initio molecular dynamics (AIMD) simulations demonstrate that even if the C-H/p interacting solvent molecule is displaced from the complex, another would quickly take its place, thus maintaining the interaction. Hence, the current work shows how non-covalent interactions between solvent and substrate can enhance the rate of the reaction and expands our understanding of the role and influence of the solvent in effecting important chemical transformations.

Catalytic reductive deoxygenation of esters to ethers driven by hydrosilane activation through non-covalent interactions with a fluorinated borate salt - Rysak, Vincent; Dixit, Ruchi; Trivelli, Xavier; Merle, Nicolas; Agbossou-Niedercorn, Francine; Vanka, Kumar; Michon, Christophe (Catalysis Science & Technology, 2020)
We report the catalytic and transition metal-free reductive deoxygenation of esters to ethers through the use of a hydrosilane and a fluorinated borate BArF salt as a catalyst. Experimental and theoretical studies support the role of noncovalent interactions between the fluorinated catalyst, the hydrosilane and the ester substrate in the reaction mechanism.

Computational insights into the role of external and local electric fields in macrocyclic chemical and biological systems - Mukherjee, Anagh; Ghule, Siddharth; Vanka, Kumar (ChemPhysChem, 2021)
The investigation of the role of the electric field in systems of widespread interest employing computational techniques is an emerging area of research. The outcome of applying an oriented external electric field (OEEF) on the geometric and electronic properties of the chemically unique pi-conjugated cyclic carbon ring compounds has been explored with density functional theory (DFT). Distinct changes in the structural and electronic features of such ring compounds are observed upon the application of OEEFs. Importantly, the calculations indicate that a mixed aliphatic-aromatic conjugated ring converts from a singlet to a triplet after the application of an OEEF, suggesting potential applications in optoelectronics for such molecules, without the need for photochemically induced change in the spin state. Furthermore, the influence of built-in local electric fields (LEFs) present in naturally occurring macrocyclic systems such as valinomycin has also been explored. Static and ab initio molecular dynamics (AIMD) calculations indicate that LEFs are the primary driving factor in determining the energetically favoured position of counter anions such as chloride (Cl-) in the potassium (K+) and sodium (Na+) coordinated valinomycin macrocycle structures: they exist inside the cage in the case of K+ sequestration by valinomycin and outside for Na+. This divergence has been proposed to be the determining factor for the selectivity of the valinomycin macrocycle for binding a K+ cation over Na+.
Keywords: counter anions; Density functional calculations; electric field; ion selectivity; macrocyclic systems

Computational insights into hydroboration with acyclic alpha-Borylamido-germylene and stannylene catalysts: Cooperative dual catalysis the key to system efficiency - Banerjee, Subhrashis; Vanka, Kumar (Polyhedron, 2022)
The chemistry of low valent main group compounds has grown as an alternative to the chemistry of less abundant and less green transition metal complexes. It has been found that low valent compounds such as carbenes, silylenes, stannylenes and germylenes are efficient for activating small molecules and for catalysis. However, the reaction mechanism and the factors that affect the rate of reaction are not completely understood. In this computational investigation with density functional theory (DFT), we investigate and demonstrate the efficiency of a new mechanism for the hydroboration of aldehydes by germylenes and stannylenes, in the presence of the common hydroborating agent, pinacolborane, HBpin. This mechanism involves an HBpin molecule as an additional catalyst that cooperates with the germylene or stannylene catalyst to efficiently carry out the hydroboration. This mechanism is first demonstrated to work for experimentally reported systems, and then shown to be efficient for newly proposed germylene and stannylene systems. These new systems are alpha-Borylamido-germylene ((2,6-iPr(2)C(6)H(3)NBCy(2))(2)Ge(II)) and alpha-Borylamido-stannylene((2,6-iPr(2)C(6)H(3)NBCy(2))(2)Sn(II)). These new insights will help researchers look into low valent germylene and stannylene chemistry from a new perspective.
Keywords: Catalysis of hydroboration; computational chemistry; Germylenes and stannylenes; Main group chemistry; New mechanism

Cocrystal approach to modulate the photoluminescent properties of a GFP chromophore analogue: role of halogen/hydrogen bonding in achieving a wide range of solid-state fluorescence emissions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Annadhasan, Mari; Biswas, Anupam; Manoj, Kochunnoonny; Vanka, Kumar; Gonnade, Rajesh G. (Crystal Growth & Design, 2023)
Fine-tuning the photophysical properties of fluorescentorganicsolids is essential to attain multicolor displays and meet the demandfor futuristic light-emitting materials. Here, we report the tunableluminescence of a green fluorescent protein (GFP) chromophore analogue,3,4,5-TIA (A), based on the formation of two-component molecular cocrystalswith six different coformers. Coformers selected to synthesize thebinary cocrystals include 1,4-diiodotetrafluorobenzene (B), perfluoronaphthalene(C), 1,4-dibromotetrafluorobenzene (D), 2,3,5,6-tetrafluoroterephthalicacid (E), benzene-1,2,4,5-tetracarbonitrile (F), and benzene-1,2,4,5-tetracarboxylicacid (G). Interestingly, the cocrystals A center dot C and A center dot Fshowed molecular crystal polymorphism with a slight variation in fluorescence,revealing an aggregation-induced emission (AIE). A crystal structureanalysis showed the interplay of hydrogen bonding, halogen bonding,and aromatic pi-stacking interactions in associating neutralsolid components in the cocrystal. All of the novel cocrystals displayeda wide range of photoluminescence ranging from blue to dark orange.The time-dependent density functional theory (TD-DFT) calculationsindicate the changes in the energy level structures (HOMO to LUMO)in cocrystals that resulted in variations in fluorescence emission.The study aims to further understand the structure-propertyrelationship between molecular arrangement and photoluminescence. Cocrystals of a GFPc analogue with differentcoformers displayeda wide range of fluorescence emissions ranging from blue to dark orangewith varying quantum yields. With similar geometries of pi-stackinginteractions, hydrogen and halogen bonding have played a vital rolein fine-tuning the photoluminescence; halogen bonding leads to a blueshift, and hydrogen bonding results in a red shift.

On the competition between six-membered and five-membered NHC towards alane centered ring expansion - Balayan, Kajal; Sharma, Himanshu; Vanka, Kumar; Ravindranathan, Sapna; Gonnade, Rajesh G.; Sen, Sakya S. (Chemical Communications, 2023)
The combination of 6-SIDipp center dot AlH3 (1) and 5-IDipp resulted in the ring expansion of 6-NHC, while the five-membered NHC remained unchanged, which was subsequently explained by DFT studies. Besides, the substitution chemistry of 1 was also studied with TMSOTf and I-2, which gave rise to the substitution of a hydride by triflate or iodide ligands.

Computational insights into the iron-catalyze d magnesium-me diate d hydroformylation of alkynes - Sharma, Himanshu; Tewari, Tanuja; Chikkali, Samir H.; Vanka, Kumar (Journal of Organometallic Chemistry, 2023)
Iron is one of the most abundant transition metals in the earth's crust. It has attracted a lot of attention due to its low toxicity, bio-compatibility, and high natural abundance. Iron-catalyzed hydroamination, hydroalkoxylation, hydrocarboxylation, hydrosilylation, hydroboration, hydrophosphination, hydromagnesiation, and carbonylation reactions have therefore been developed over the past decades. However, despite many experimental and theoretical studies, a complete mechanistic understanding of iron-catalyzed hydrofunctionalisation at the molecular level has not yet been achieved. In this work, through density functional theory (DFT) calculations, we have shown the most feasible path for the hydroformylation of alkynes for an experimentally studied system. We have looked at the iron salt as a precatalyst without any external donor ligand, and the calculations revealed that hydrometalation followed by beta-hydride elimination was favorable over the direct migration of the beta-hydrogen to carbon. Furthermore, our calculations show that the solvent plays an important role in the hydromagnesiation reaction. Furthermore, we have employed an explicit solvent model, where the attachment of one molecule of solvent to the iron center was seen to stabilize the transition states significantly.(c) 2023 Elsevier B.V. All rights reserved.
Keywords: Computational study; Ethylene Assisted Catalysis; EtMgBr Assistance; Explicit Role of Solvent; Hydroformylation; Iron Catalyst

Controlled reduction of isocyanates to formamides using monomeric magnesium - Kumar, Rohit; Sharma, Vishal; Banerjee, Subhrashis; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2023)
This work describes a transition metal-free methodology involving an efficient and controlled reduction of isocyanates to only formamide derivatives using pinacolborane (HBpin) as the hydrogenating agent and a bis(phosphino)carbazole ligand stabilized magnesium methyl complex (1) as the catalyst. A large number of substrates undergo selective hydroboration and give exclusively N-boryl formamides.

Crystal engineering for intramolecular π-π stacking: effect of substitution of electron-donating and electron-withdrawing groups on the molecular geometry in conformationally flexible Sulfoesters and sulfonamides - Shaikh, Samir R.; Gawade, Rupesh L.; Dabke, Niteen B.; Dash, Soumya R.; Vanka, Kumar; Gonnade, Rajesh G. (CrystEngComm, 2024)
A series of 21 sulfoester and sulfonamide derivatives comprising two aromatic rings was synthesized to investigate the effect of the presence of either electron-donating (ED) or electron-withdrawing (EW) groups on the intramolecular pi-stacking assembly. The positioning of ED or EW moieties was carried out directly on one of the aromatic rings linked to the sulfonyl or sulfonamide moieties. In contrast, the other aromatic ring (phenyl or pyridine) was connected by a -CH2-CH2- spacer with the sulfonyl or sulfonamide moiety. The purpose of having an ethyl spacer between the two aromatic rings was to achieve conformational flexibility, facilitating the intramolecular pi-stacking assembly between the two aromatic rings. The use of sulfoester/sulfonamide groups allowed more conformational flexibility to attain desired orientations in solids with the interplay of the hydrogen-bonding interactions. Between the two functional groups, sulfonamides offered a more hydrogen-rich environment due to the amine moiety and may exhibit higher H-bonding propensity than the sulfoester moiety. The central idea here was to study the interplay between the hydrogen-bonding and pi & ctdot;pi interactions. The substituent groups chosen were categorized as strong electron-withdrawing (-CF3 and -CN), weak electron-withdrawing (-Cl and -Br), neutral (-H), and good electron-donating (-CH3 and -OCH3) groups. Crystal structure analysis revealed the syn conformation for all the derivatives, enabling intramolecular pi & ctdot;pi interactions between the two aromatic rings, whereas in the sulfonamide derivatives, the molecule takes either midway or anti conformations, except for one pyridine sulfonamide derivative, which showed the syn orientation but lacked intramolecular pi-stacking interactions. The absence of any conventional H-bond forming functional groups in the sulfoester derivatives may have resulted in the syn geometry facilitated by intramolecular pi-stacking interactions. Conversely, H-bond-forming functional groups in the sulfonamide derivatives could have prevented the syn conformation. The conformational analysis carried out employing density functional theory (DFT) calculations confirmed the higher stability of the syn conformation over the midway and anti orientations. The placing of electron-withdrawing and electron-donating groups at the para position of the benzene revealed sulfoesters preferably adopts a syn geometry facilitating the intramolecular pi-stacking, but sulphonamides takes midway or anti-geometry.

Ce[N(SiMe3)2]3(THF)3-catal yzed hydroboration of CO2, esters and epoxides with pinacolborane: selective synthesis of methanol in multigram scale - Hossain, Md Jabed; Shah, Brij Kumar; Dash, Soumya Ranjan; Vanka, Kumar; Khan, Shabana (Chemistry-A European Journal, 2025)
In this work, we have reduced CO2 with HBpin to afford borylated methanol product selectively in similar to 99 % yield using Ce[N(SiMe3)(2)](3)(THF)(3) as a catalyst. This led to multigram scale isolation of methanol obtained from CO2 reduction via the hydrolysis of borylated methanol, this establishes the potential of Ce[N(SiMe3)(2)](3)(THF)(3) as an efficient homogeneous catalyst for the bulk scale methanol synthesis. A practical application of this catalytic system was also shown by reducing CO2-containing motorbike exhaust efficiently and selectively. Further, C-O bond activation of esters and epoxides using HBpin and 1-2 mol % of Ce[N(SiMe3)(2)](3)(THF)(3) at 60 degrees C afforded the borylated alcohols in good to excellent yields, which can easily be hydrolysed to the eco-friendly corresponding alcohol. The stoichiometric experiments were performed to prove the formation of in-situ generated cerium hydride [Ce]-H as an active catalyst.
Keywords: Cerium; CO2 reduction; Epoxide; Ester; Hydroboration; Lanthanides

Cocrystals of the green fluorescence protein chromophore analogue: coformer-induced switch between AIE and ACQ - Suresh, Sneha; Dabke, Niteen B.; Pandya, Rinu; Vanka, Kumar; Dutta, Madhusudan; Gonnade, Rajesh G. (Crystal Growth & Design, 2025)
Fluorescent organic solids hold great potential for advancing photonics applications. However, tuning their solid-state photoluminescent emissions remains a significant challenge. In this study, we report the synthesis and characterization of five cocrystals (two cocrystal polymorphs) derived from a pristine imidazolinone derivative (A) and the various coformer molecules, namely 1,2,4,5-tetrafluoro-3,6-diiodobenzene, 1,2,4,5-tetrafluoro-3,6-dibromobenzene, perfluoronaphthalene, and 3,4,5-trifluorobenzoic acid. The structural and optical properties of these cocrystals were examined by using single-crystal X-ray diffraction, absorption spectroscopy, photoluminescence spectroscopy, and photoluminescence decay spectroscopy. Cocrystals I, II, and III are isomorphous pairs and exhibit three-dimensional isostructurality, where the coformer molecules bridge adjacent helices of compound A, leading to aggregation-induced emission. In contrast, the cocrystal polymorphs IVA and IVB developed using coformer 3,4,5-trifluorobenzoic acid form two-dimensional sheet-like structures mediated by pi-stacking interactions between the coformers and molecule A, with interplanar distances ranging from 3.2 to 3.5 & Aring;. These stronger pi-pi interactions promote nonradiative decay pathways, resulting in reduced or quenched fluorescence and an aggregation-caused quenching effect. To gain further insights into their electronic properties, theoretical analysis including frontier molecular orbitals, time-dependent density functional theory, Hirshfeld surface analysis, molecular electrostatic potential, and noncovalent interaction plots were performed.

The critical helping hand of water: theory shows the way to obtain elusive, granular information about kinetic asymmetry driven systems - Bajpai, Priyam; Thulasiram, Shrivatsa; Vanka, Kumar (Chemical Science, 2025)
Kinetic asymmetry is crucial in chemical systems where the selective synthesis of one product over another, or the acceleration of specific reaction(s) is necessary. However, obtaining precise information with current experimental methods about the behavior of such systems as a function of time, substrate concentration and other relevant factors, is not possible. Computational chemistry provides a powerful means to address this problem. The current study unveils a two-pronged computational approach: (i) full quantum chemical studies with density functional theory (DFT), followed by (ii) stochastic simulations with a validated Gillespie algorithm (GA) (using representative model systems where necessary), to study the behavior of a kinetic asymmetry driven unidirectional molecular motor (1-phenylpyrrole2,2 `-dicarboxylic acid) (Nature, 2022, 604 (7904), 80-85). Our approach allows us to understand what is really taking place in the system, underlining the crucial role played by water molecules in facilitating the rotation of the motor. It is seen that water lubricates the motion by increasing the rotation rate constant of the final step by, remarkably, more than ten orders of magnitude! These insights further serve to explain the efficient rotation of the very recently reported gel-embedded molecular motor (Nature, 2025, 637 (8046), 594-600), providing an upper limit for the allowed rotation barrier in such systems, and thus also casts light into the functioning of bio-molecular motors. The current work therefore provides a template for carefully and properly studying a wide variety of important, kinetic asymmetry driven systems in the future.